Developing Language Through Science. (30th November 2021) - Gerde, Hope K.; Wasik, Barbara A.
Abstract: Teaching science can provide opportunities for young children to explore and learn about the world around them and, equally important, to support children's language development. Yet, recent research suggests that children's access to science education is limited, especially in early and elementary education. Since language is critical to children's success in learning to read, teachers need access to a variety of venues to develop these foundational literacy skills. This paper provides evidence of the importance of teaching science in an effort to teach science ideas and develop children's language. In addition, this paper describes a range of approaches teachers can use to facilitate inquiry‐based science education and oral language development simultaneously. When educators engage children in high‐quality science experiences, they present children with the opportunity to develop both science ideas and language.